Chylous mesenteric cyst–post trauma challenge: a case report - Ghafoor, Ayesha; Muhammad Nouman Rafique; Muhammad Bilal Chishti; Noor-Ul-Mubeen; Ayesha Rafique; Muhammad Waris Farooka (Journal of the Pakistan Medical Association, 2025)
Mesenteric cysts are rare intra-abdominal lesions often presenting diagnostic challenges due to their non-specific clinical manifestations. Despite its rarity, mesenteric cyst should be considered in patients with abdominal masses, especially those with a history of trauma. Diagnostic imaging, such as ultrasound and computerised tomography scan, aids in characterisation and surgical planning. Surgical excision remains the mainstay of treatment, offering favourable outcomes and reducing the risk of recurrence and malignancy. We report the case of a 15-year-old male with progressively enlarging abdominal swelling following blunt abdominal trauma, who was ultimately diagnosed with a chylous mesenteric cyst. This case underscores the importance of considering traumatic mesenteric cysts in the differential diagnosis of abdominal lesions. Keywords: Mesenteric cyst, Trauma, Chylous, Excision.